Pengaruh Variabel Makroekonomi Terhadap Indeks Saham Syariah Indonesia (Issi) Di Bursa Efek Indonesia Periode Januari 2014 - Juli 2016 - Karlina, Kiki; , Eni Setyowati, S.E, M.Si; , Drs. Harun, M.H (2017)
The aims of this study is to determine whether there is influence inflation, interest rates, Money Supply (M2) and exchange rate against Indonesian Sharia Stock Index (ISSI). This study uses secondary data (time series) monthly from the period 2014: 01-2016: 07. The analytical tool used in this study is a partial adjustment regression model (PAM: Partial Adjustment Model) and Classical Assumption Test treated with Quantitative Micro Soffware E-Views Based on the test results Partial Adjustment Model (PAM) indicated that the variable inflation and interest rates in the long term and short term showed no effect on Sharia Stock Index Indonesia (ISSI), a variable amount of money supply (M2) in the short and long term shows a positive influence and significant impact on Indonesia Sharia Stock Index (ISSI), while the exchange rate variable in the long term and short term showed negative and significant impact on Indonesia Sharia Stock Index (ISSI). Furthermore, from the results of the classical assumption in mind that the models used in the study is no problem in the test for normality, autocorrelation, heteroscedasticity, and model specifications. But the problem is only in multicolinierity test.